Ethical Responsibilities to Adults with Communication Impairments Involved in Group Therapy - Elman, Roberta J. (Seminars in Speech and Language, 2020)
Ethical challenges can arise when providing group therapy to adults living with communication impairments. In addition to the ethical challenges that may be encountered when conducting one-to-one therapy intervention, practitioners must also consider dilemmas that are specific to group therapy. This article considers the principles and rules of the American Speech-Language-Hearing Association (ASHA) Code of Ethics via a series of clinical vignettes that illustrate four ethical challenges that may be encountered when providing group therapy: acquiring sufficient clinical competency to conduct group therapy; handling issues related to client confidentiality; resisting external pressure to provide groups solely for financial gain and/or other administrative efficiencies; and handling practitioner–client boundaries.
Keywords: group therapy; competent care; professional ethics; professional conduct